Pengaruh Citra Merek, Daya Tarik Iklan Dan Kepercayaan Merek Terhadap Minat Beli Tissue Merek Multi Di Kota Batam - Alwen Cleavelano; Winda Evyanto (eCo-Buss, 2024)
This research can provide a goal to analyze how brand image, advertising attractiveness and brand trust can have a partial or simultaneous influence on the intention to buy tissue brand Multi in Batam City. This type of research can use a type of research which is a type of descriptive with quantitative research methods, the population used is a buyer of tissue brand Multi in the city of Batam, totaling 101 respondents with a sampling technique using non-probability sampling. In the data analysis method, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis (R2), t test and f test can be used. Based on the research findings, there is a relationship between brand image and purchase intention which can be concluded from the results of the t test, namely 3.184 > t table 1.984. These results show a positive value and have a significance of 0.002 <0.05. There is a relationship between advertising attractiveness and buying interest which can be concluded from the results of the t test, namely 7.077 > t table 1.984. These results show a positive value and have a significance of 0.000 <0.05. There is a relationship between brand trust and purchase intention which can be concluded from the results of the t test, namely 3.299 > t table 1.984. These results show a positive value and have a significance of 0.001 <0.05. Simultaneous test results produce a value of 102.121 > f table 2.70, namely a positive and significant score of 0.000 <0.05. According to research findings, brand image, advertising attractiveness and brand trust as a whole have a positive and significant effect on the intention to buy tissue brand Multi in Batam City.